Recopilación, vida y obra artística del maestro artista Nestor Ariel Castro Sarmiento (2021)
Research on the life and artistic management of the master Nestor Ariel Castro Sarmiento, in the community of the House of Culture of the municipality of Chocontá Cundinamarca, during the years 2010 - 2016, supported by the research methodology of the author Hernández Sampieri (2010), with an autobiographical research approach, focused on qualitative methodology. His legacy in the dance field is made known, delving into topics such as: experience in cultural management, folk dance and the notion of the master artist (MA). The data will emerge little by little, through the exploration, description and understanding of the evidence in text or image found in the investigation, the collection will be done through: interviews, documentary review, analysis of images and audiovisual pieces. At the end of this process, it is expected to benefit the population of the house of culture of the municipality of Chocontá Cundinamarca, with a bibliographic document that is easily accessible to the community